Effect of motor relearning program poststem cell therapy in chronic stroke - Jorida Fernandes; Sanjiv Kumar (Journal of the Scientific Society, 2017)
A 59-year-old male, with chronic hemiplegia, received the first dose of stem cell therapy 1 year back. Physiotherapy was started immediately. The patient was evaluated using Fugl-Meyer assessment scale and functional independence measure before and after physiotherapy. After 6 months of physiotherapy intervention using motor relearning program, improvements were observed in the motor outcome with significant changes in the upper extremity, especially the hand component.